Novel aspects of parenchymal–mesenchymal interactions: from cell types to molecules and beyond - Bluguermann, Carolina (2013)
Mesenchymal stem or stromal cells (MSCs) were initially isolated from the bone marrow and received their name on the basis of their ability to differentiate into multiple lineages such as bone, cartilage, fat and muscle. However, more recent studies suggest that MSCs residing in perivascular compartments of the small and large blood vessels play a regulatory function supporting physiologic and pathologic responses of parenchymal cells, which define the functional representation of an organ or tissue. MSCs secrete or express factors that reach neighbouring parenchymal cells via either a paracrine effect or a direct cell-to-cell interaction promoting functional activity, survival and proliferation of the parenchymal cells. Previous concept of ´epithelial-stromal´ interactions can now be widened. Given that MSC can also support hematopoietic, neuronal and other non-epithelial parenchymal lineages, terms ´parenchymal-stromal´ or ´parenchymal-mesenchymal´ interactions may better describe the supportive or ´trophic´ functions of MSC. Importantly, in many cases, MSCs specifically provide supportive microenvironment for the most primitive stem or progenitor populations and therefore can play a role as ´stem/progenitor niche´ forming cells. So far, regulatory roles of MSCs have been reported in many tissues. In this review article, we summarize the latest studies that focused on the supportive function of MSC. This thread of research leads to a new perspective on the interactions between parenchymal and mesenchymal cells and justifies a principally novel approach for regenerative medicine based on co-application of MSC and parenchymal cell for the most efficient tissue repair.